Magic mirror on the wall, which is the best meta-analysis one of all? - Taccone, Fabio Silvio (Critical care (London, England), 2023)
[...]the presence of substantial uncertainty in the results suggests the possibility of a minimally clinically important difference, which may have been influenced by patient selection. [...]it cannot be excluded that a subset of patients may indeed benefit from hypothermia treatment. [...]there is a need for improved patient selection criteria to identify those individuals at high-risk of moderate brain injury, i.e., those who are not too mildly affected, as they may not require a specific neuroprotective strategy, and not too severely affected, as they may have poor prognosis regardless of any intervention. Fernando SM, Di Santo P, Sadeghirad B, Lascarrou JB, Rochwerg B, Mathew R, Sekhon MS, Munshi L, Fan E, Brodie D, Rowan KM, Hough CL, McLeod SL, Vaillancourt C, Cheskes S, Ferguson ND, Scales DC, Sandroni C, Nolan JP, Hibbert B. Targeted temperature management following out-of-hospital cardiac arrest: a systematic review and network meta-analysis of temperature targets.